Improving The Learning Outcomes Of Passing In Football Games Using The Drill Method In Class IX 4 Students At SMP Negeri 3 Palembang - Emilius Surya; Hartati (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
The Drill Method is a way of education students by carryng out training activities, so that students have better skills than before. There were many scores that were below the criteria. This is evidenced by only 60% of the overall population of learners. In view of this objective, a Classroom Action Research (PTK) using the drill metod to improve the learning outcomes of students in class IX. 4 at SMP Negeri 3 Palembang. After using a methodology that combines the drill method and interactive games. This method was implemented in two cycles, each cycles consisted of two games. In cycle there was an increase from 60% to 70%. In addition, during cycle II, there was a significant increase from 70% to 80% which mirrored the improvement observed in cycle I. Based on these findings, it can be concluded that the use of practice and game techniques can improve educational achievement in delivering the material.